New Information about the Characteristics of Medicinal Plants - Tokhirov Bakhtiyor Bakhshullayevich; Asrorova Odinaoy Otabekovna; Sayfiyev Tokhir Fakhriddinovich (Researchparks Publishing, 2021)
The demand for medicinal plants is growing. Therefore, the study of medicinal plants, the study of their effects on diseases, the preparation of medicines from them are important topics. This article provides the latest information on the cultivation of medicinal plants, the impact of medicinal plants on diseases and the preparation of medicines from them in medicine.